The Consequences of Using AI in the Perspective of John Paul II’s Teaching - Jaworski, Tomasz (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The article examines the philosophical anthropology developed by Karol Wojtyła (John Paul II) as a lens for understanding artificial intelligence. It contrasts technological determinism with Catholic personalism as complementary answers to the question, “What does it mean to be human?” The advent of AI underscores the irreducible unity of action and intention in the human act: algorithms can mimic behaviour but cannot reach the metaphysical truth or moral meaning of deeds. Drawing on John Paul II’s teaching on dignity, freedom, and relationality, the paper critiques the anthropomorphising of AI and underscores the scientific method’s limits in grasping the full reality of the person phenomena. It calls for a balanced stance—between scientific materialism and non-materialist reflection—so that AI advances genuinely empower human autonomy.